Looking Back: Towards a Socialist America - Clawson, Mary Ann (Radical Teacher, 2023)
Using original course documents and interviews with early participants, this essay contextualizes and reflects on Arnesen, Ebb, Rome, and Ward's account of a nineteen-seventies model for "teaching about socialism."